Year 1: Pollinating My Doctoral Journey - Wilson, Shari L. (My University, 2020)
Biodiversity is decreasing around the world. An international network for teachers and students to utilize in growing biodiverse schoolyards would make much more habitat available. Questions to ask include: How can schoolyards help increase biodiversity? What tools do schools need to manage schoolyards for biodiversity?